The Sexual Disgust Questionnaire; a Psychometric Study and a First Exploration in Patients with Sexual Dysfunctions. (22nd October 2012) - van Overveld, Mark; de Jong, Peter J.; Peters, Madelon L.; van Lankveld, Jacques; Melles, Reinhilde; ter Kuile, Moniek M.
ABSTRACT Introduction. Disgust may be involved in sexual problems by disrupting sexual arousal and motivating avoidance of sexual intercourse. To test whether heightened disgust for sexual contaminants is related to sexual dysfunctions, the Sexual Disgust Questionnaire (SDQ) has recently been developed. Previous research showed that particularly women with vaginismus display a generally heightened dispositional disgust propensity and heightened disgust toward stimuli depicting sexual intercourse. Aim. To determine the psychometric properties of the SDQ and test whether heightened disgust toward sexual stimuli is specific to vaginismus or can be observed in other sexual dysfunctions as well. Methods. First, a large sample of undergraduates and university employees completed the SDQ (N = 762) and several trait disgust indices. Next, women with vaginismus (N = 39), dyspareunia (N = 45), and men with erectile disorder (N = 28) completed the SDQ and were compared to participants without sexual problems (N = 70). Main Outcome Measure. SDQ to index sexual disgust. Results. The SDQ proved a valid and reliable index to establish disgust propensity for sexual stimuli. Supporting construct validity of the SDQ, sexual disgust correlated with established trait indices. Furthermore, sexual disgust and willingness to handle sexually contaminated stimuli were associated with sexual functioning in women, but not in men. Specifically women with vaginismus displayed heightened sexual disgust compared to women without sexual problems, while men with erectile disorders demonstrated a lower willingness to handle sexually contaminated stimuli compared to men without sexual problems. Conclusions. The SDQ appears a valid and reliable measure of sexual disgust. The pattern of SDQ‐scores across males and females with and without sexual dysfunctions corroborates earlier research suggesting that disgust appraisals are involved especially in vaginismus and supports the view that the difficulty with vaginal penetration experienced by women in vaginismus may partly be due to disgust‐induced defensive reflexes that could disrupt sexual arousal. van Overveld M, de Jong PJ, Peters ML, van Lankveld J, Melles R, and ter Kuile MM. The Sexual Disgust Questionnaire; a psychometric study and a first exploration in patients with sexual dysfunctions. J Sex Med **;**:**–**.